(untitled) (Medico Legal Update, 2021)
Objective: The objective of this researchis to develop and validate a solid and reasonablescale to measure the failure of students in Morocco. Material and Method: This is a cross-sectional study, which took place between November 2019 and March 2020. The internalreliability of the questionnaire waschecked by calculating the Cronbach’s Coefficient Index, and a factor analysis was performed. Results: The population of ourstudyis 184 students of three masters in teaching and education, University Ibn Tofail of Kenitra-Morocco. The averageage at the time of enrollment in the first-year master’s degreeis 26.59±5.65 years. Regarding gender, wenoted that males represent a percentage of 71.2% (n=131), while females represent 28.8% (n=53) with a sex ratio (m/f) of 2.4 (p<0.005). The Cronbach’s alpha value for all items was 0.84. Similarly, the calculation of Cronbach’s alpha showed homogeneityacross the different dimensions of the questionnaire. For the professional curriculum (?=0.93), motivation (?=0.97), educational satisfaction (?=0.93), abandonment of university studies (?=0.96) and non-academic curriculum of students (?=0.87). Conclusion: Based on the results of ourstudy, wecould, therefore, measure the academic failure of students in the education and teaching tradestreams using a questionnaire.